Religious leaders' role in pregnant and breastfeeding women's decision making and willingness to use biomedical HIV prevention strategies: a multi-country analysis. Issue 5 (13th April 2022) - Young, Alinda; Ryan, Julia; Reddy, Krishnaveni; Palanee-Phillips, Thesla; Chitukuta, Miria; Mwenda, Wezi; Kemigisha, Doreen; Musara, Petina; van der Straten, Ariane; ,
Abstract: Oral Pre-Exposure Prophylaxis (PrEP) is an established option, and the dapivirine vaginal ring is emerging as a promising strategy for HIV prevention option for women. Because of this, understanding the contextual and cultural factors that will support the increased uptake of these products is crucial. In sub-Saharan Africa, religious leaders may be important stakeholders to involve in product information, education and roll-out. We conducted a sub-analysis of data from 232 participants taking part in the MTN-041/MAMMA study to explore religious leaders' involvement in pregnant and breastfeeding women's health. Study participants viewed biomedicine and spirituality as interlinked and believed that women could seek health-related care from medical experts and turn to faith-based organisations for religious or spiritual needs. Religious leaders were invested in the health of their congregations, endorsed a variety of sexual health strategies, and were eager to learn more about emerging HIV prevention technologies. These data signal the role of religious leaders in supporting their communities, and the importance of involving religious leaders in efforts to roll out new HIV prevention products to facilitate uptake.